Engaged by the Revolution: the Lepsis Chekist family in Vyatka (1919) - A. S. Pozdnyakova (Омский научный вестник: Серия "Общество. История. Современность", 2023)
Based on unpublished sources from the funds of the State Archive of the Kirov region and memoir journalism, the article analyzes a fragment of the life path of the spouses of security officers R. K. Lepsis and A. I. Lepsis associated with their service in Vyatka during the Civil War. The purpose of the work is to use the example of a single married couple of security officers to indicate the factors that influenced the life of the family in the era of social cataclysms. The theoretical basis of the study is the anthropological approach. In conclusion, the author emphasizes that the study of the Lepsis family makes it possible to reconstruct the image of a Soviet person, to get to the problems of gender history.